DETERMINATION OF TRANSFORMATIONAL LEADERSHIP, EDUCATION AND WORK DISCIPLINE WITH WORK SPIRIT AS A MEDIATOR VARIABLE ON EMPLOYEE PERFORMANCE TAX MANAGEMENT AGENCY AND RETREBUTION FOR THE CITY OF BATAM - Rajesh Rila; Indrayani Indrayani; Ayu Rahmasari; Reny Nozariyanti; Muammar Khaddafi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
In this study, researchers used data respondents, such as gender, age and long working respondents to provide information on the characteristics of respondents. The questionnaire was spread over 52. The discussion in this chapter is the result of field studies to obtain data on the questionnaire responses that measure five key variables in the study, namely transformational leadership, education, work discipline, work spirit and employee performance. Analysis of data with parametric and non parametrics statistics using SEM-PLS (structural Equation Modelling-Partial Least Square) on the research variables, instrument test, normality test, hypothesis test, as well as discussion of the hypothesis test results and path analysis Path. This research uses path analysis to test relationship patterns that reveal the influence of variables or a set of variables against other variables, both direct influences and indirect influences. Calculation of line coefficient in this study assisted with Smart PLS Ver 3.0. To find out the direct and indirect influences between variables then be seen from the calculation result of the line coefficient and to know the significance. The effect of the X3 variable against X4 has a P-Values value of 0.032 < 0.05, so it can be stated that the effect between X3 against X4 is significant. The effect of the variable X3 against Y has a P-Values value of 0.003 < 0.05, so it can be stated that the influence between X3 to Y is significant. The effect of the variable X3 against Y has a P-Values value of 0.003 < 0.05, so it can be stated that the influence between X3 to Y is significant. The effect of the variable X3 against Y has a P-Values value of 0.003 < 0.05, so it can be stated that the influence between X3 to Y is significant. The effect of a X1 variable against Y has a P-Values value of 0.006 < 0.05, so it can be stated that the effect between X1 to Y is significant. The effect of a X1 variable against Y has a P-Values value of 0.006 < 0.05, so it can be stated that the effect between X1 to Y is significant. The effect of a variable X2 against Y has a P-Values value of 0.011 < 0.05, so it can be stated that the effect of the X2 against Y is significant.